Deep Learning dengan Pendekatan Kontekstual Terintegrasi Kearifan Lokal Tapanuli: Studi Validitas dalam Pengembangan Model Pembelajaran Ekonomi - Sari, Erlina; Ardiana, Nunik; Ahmad, Marzuki (Universitas Hamzanwadi, 2025)
This research is based on the era of digital transformation and the Industrial Revolution 4.0, which demands education that is adaptive to technology and involves a contextual approach integrated with local wisdom. The problem in this research is the implementation of economic learning, which tends to rely on conventional learning models and underutilise students' critical thinking skills. This study aims to develop a learning model that combines the Deep Learning model, the Contextual Approach, and Tapanuli Local Wisdom that can teach students critical thinking skills. However, at this stage, the discussion focuses on the validity of the learning model product. To achieve the research objectives, the Plomp model was used, which involved the stages of Preliminary Investigation, Design, Realization/Contruction, Test, Evaluation and Revision, and product revision through product validation by five validators. The results of the study indicate the need for a learning model product that integrates deep learning, the Contextual Approach, and Tapanuli Local Wisdom. Furthermore, the model book design was found to be valid and suitable for use, with only minor revisions required. The research conducted provides a conclusion that the Deep Learning learning model, integrated with a contextual approach and local wisdom, is worthy of being tested to teach students' critical thinking skills in economics.